2020
DOI: 10.1371/journal.pone.0226840
|View full text |Cite
|
Sign up to set email alerts
|

Novel imaging biomarkers for mapping the impact of mild mitochondrial uncoupling in the outer retina in vivo

Abstract: To test the hypothesis that imaging biomarkers are useful for evaluating in vivo rod photoreceptor cell responses to a mitochondrial protonophore. Methods Intraperitoneal injections of either the mitochondrial uncoupler 2,4 dinitrophenol (DNP) or saline were given to mice with either higher [129S6/eVTac (S6)] or lower [C57BL/6J (B6)] mitochondrial reserve capacities and were studied in dark or light. We measured: (i) the external limiting membrane-retinal pigment epithelium region thickness (ELM-RPE; OCT), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 55 publications
(125 reference statements)
0
30
0
Order By: Relevance
“…We found that the RPE-specific toxin sodium iodate produces less rod mitochondrial oxidative stress and rod death in 129S6/ev mice than in C57BL/6J mice (Berkowitz et al, 2017;Berkowitz et al, 2018b). Further, 129S6/ev mice retina have an 11% greater mitochondrial reserve than C57BL/6J mice from The Jackson Laboratory as measured by an ex vivo Seahorse assay (Berkowitz et al, 2018b;Berkowitz et al, 2020). When compared in vivo with those of dark-adapted C57BL/6J mice, rod mitochondria of dark-adapted 129S6/ev mice have a greater capacity to respond to a protonophore-evoked shrinkage of the ELM-RPE region as measured by OCT, consistent with the signaling pathway in Fig.…”
Section: Oxidative Stress Impairment Of Subretinal Space Hydration Inmentioning
confidence: 83%
“…We found that the RPE-specific toxin sodium iodate produces less rod mitochondrial oxidative stress and rod death in 129S6/ev mice than in C57BL/6J mice (Berkowitz et al, 2017;Berkowitz et al, 2018b). Further, 129S6/ev mice retina have an 11% greater mitochondrial reserve than C57BL/6J mice from The Jackson Laboratory as measured by an ex vivo Seahorse assay (Berkowitz et al, 2018b;Berkowitz et al, 2020). When compared in vivo with those of dark-adapted C57BL/6J mice, rod mitochondria of dark-adapted 129S6/ev mice have a greater capacity to respond to a protonophore-evoked shrinkage of the ELM-RPE region as measured by OCT, consistent with the signaling pathway in Fig.…”
Section: Oxidative Stress Impairment Of Subretinal Space Hydration Inmentioning
confidence: 83%
“…In this scenario (summarized in Fig 10 ), elevating cGMP levels in light-adapted mice causes sustained opening of rod photoreceptor outer segment cyclic nucleotide-gated channels, an energy-intensive event [ 64 ]. As a result of this increase in mitochondrial respiration, the subretinal space fills with acidified waste-water [ 14 , 17 19 , 24 , 28 , 65 ]. The lowering of the subretinal space pH upregulates water removal co-transporters in RPE with the end result of dehydrating / thinning of the ELM-RPE space ( Fig 10 ) [ 14 , 17 19 , 24 , 28 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of this increase in mitochondrial respiration, the subretinal space fills with acidified waste-water [ 14 , 17 19 , 24 , 28 , 65 ]. The lowering of the subretinal space pH upregulates water removal co-transporters in RPE with the end result of dehydrating / thinning of the ELM-RPE space ( Fig 10 ) [ 14 , 17 19 , 24 , 28 , 65 ]. Evidence for subretinal space thinning following sildenafil is shown in Fig 3 [ 14 , 17 19 , 24 , 28 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous quantitative studies performed in P40 or older WT C57BL/6J mice indicate a cGMP / mitochondria / pH / water removal signaling pathway that causes ELM-RPE to be measurably thinner in the dark than in the light; this phenotype is apparent in a representative P20 WT C57BL/6J mouse, which also demonstrates a clear dark less than light ELM-RPE thickness difference, as shown in Figure 1B. 40,41,[49][50][51][52][53][54][55][56] In contrast, male P24 Pde6brd10 mice lack a statistically significant dark-light ELM-RPE difference (inferior = -1.31; 95% confidence interval [CI] = -3.29 to 0.66; superior = -2.53, 95% CI = -5.56 to 0.49; P > 0.05 for both), consistent with a panretinal PDE6B mutation-induced increase in cGMP levels in the light (see Fig. 1C).…”
Section: Pde6b Mutation Suppressed the Dark Versus Light Elm-rpe Thicmentioning
confidence: 64%
“…72 For comparison, we note that WT brown 129S6/ev mice, which do not have the Nnt mutation, have an 11% greater mitochondrial reserve than C57BL/6J mice from the Jackson Laboratory as measured by an ex vivo Seahorse assay and by our OCT studies. 52,53 Further, this mutation likely affects rescue potential because sodium iodate produces less rod mitochondrial oxidative stress and rod death in 129S6/ev mice than in C57BL/6J mice. 53,73 We anticipate future studies that address this potential problem by comparing Pde6brd10 mice on the C57BL/6J background with Pde6brd10 C57BL/6 mice from a different vendor without the Nnt mutation, or with Pde6brd10 mice on the 129S6/ev background.…”
Section: Discussionmentioning
confidence: 99%